2012
DOI: 10.1002/jcla.21487
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria, Proteinuria, and Urinary Albumin to Protein Ratio in Chronic Kidney Disease

Abstract: There was a significant association between UACR and UPCR in patients with CKD. Characteristics of patients, renal function, and co-morbidities all affected UACR, UPCR, and UAPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…In contrast, another study reported that PCR was more sensitive (compared with ACR) as a screening test when proteinuria was <0.5 g/d and <1.0 g/d. (20) Consistent with our findings, many studies among CKD and non-CKD populations have shown strong correlations between ACR and PCR (14, 17–19). Yet, the recently published KDIGO guidelines strongly advocate for measurement of ACR (over PCR), partly due to limitations in measurement of PCR including substantial sample-to-sample variations in the quantity and composition of proteins and between-laboratory variations (10).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, another study reported that PCR was more sensitive (compared with ACR) as a screening test when proteinuria was <0.5 g/d and <1.0 g/d. (20) Consistent with our findings, many studies among CKD and non-CKD populations have shown strong correlations between ACR and PCR (14, 17–19). Yet, the recently published KDIGO guidelines strongly advocate for measurement of ACR (over PCR), partly due to limitations in measurement of PCR including substantial sample-to-sample variations in the quantity and composition of proteins and between-laboratory variations (10).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have found albuminuria to be superior (13), some have shown total proteinuria to be better (14), while still others have found both measures to be equivalent predictors of outcomes such as end-stage renal disease (ESRD) and mortality (15, 16). Additionally, while some studies among CKD and non-CKD populations have shown strong correlations between albuminuria and total proteinuria (14, 17–19), others have not (20). …”
mentioning
confidence: 99%
“…We used only a dipstick test to measure proteinuria. Twenty-four hour urine collections should be used to measure its constituents and albumin-to-creatinine ratios to quantify proteinuria better, confirm its prevalence,31 verify the prognostic importance and determine its incidence.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Recent analysis revealed that much of continuing increase in number of patients with CKD is seen in obese hypertensive patients. 4 Various animal models have been employed to gain more insight into the pathogenesis of CKD associated with obesity hypertension. One of the validated models is the obese Zucker rat (OZR).…”
Section: Introductionmentioning
confidence: 99%